2015
DOI: 10.1099/vir.0.000132
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal domain of Npro of classical swine fever virus determines its stability and regulates type I IFN production

Abstract: The viral protein N pro is unique to the genus Pestivirus within the family Flaviviridae. After

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…While MG132 does not directly affect the mRNA levels of ISGs in cells without CSFV (Figure 7), MG132 may regulate the expressions of ISGs through modulating the levels of related immune molecules. Viral proteins N pro , C, and p7 of CSFV have been reported to be degraded by 26S proteasome (Seago et al, 2010;Lin et al, 2014;Mine et al, 2015;Chen et al, 2019), and we have found that several other viral proteins are also affected by 26S proteasome (data not shown). Considering the relationships between CSFV viral proteins, the innate immune system and the 26S proteasome, the way that MG132 inhibits the replication of CSFV may need more detailed investigations.…”
Section: Discussionmentioning
confidence: 57%
“…While MG132 does not directly affect the mRNA levels of ISGs in cells without CSFV (Figure 7), MG132 may regulate the expressions of ISGs through modulating the levels of related immune molecules. Viral proteins N pro , C, and p7 of CSFV have been reported to be degraded by 26S proteasome (Seago et al, 2010;Lin et al, 2014;Mine et al, 2015;Chen et al, 2019), and we have found that several other viral proteins are also affected by 26S proteasome (data not shown). Considering the relationships between CSFV viral proteins, the innate immune system and the 26S proteasome, the way that MG132 inhibits the replication of CSFV may need more detailed investigations.…”
Section: Discussionmentioning
confidence: 57%
“…In a previous report, the replacement of the C-terminal of the core protein and the full-length of E rns of a CSFV vaccine strain resulted in the conversion of the END phenotype without the abrogation of its RNase activity [ 5 ]. Combined with this, this study might propose alternative critical residues for regulating the type I interferon induction, as in the case of N pro [ 34 ]. However, synergetic effects with other amino acid substitutions should be considered to clarify the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 95%
“…The N pro s of CSFV and BVDV directly bind IRF3 and induce degradation of the factor by the host proteasome, thus interfering with IFN production . According to point mutation experiments, both the protease domain and the zinc‐binding domain are essential for N pro binding to IRF3 .…”
Section: Rna‐virus Proteases Interfering With the Host Innate Immune mentioning
confidence: 99%